Perbandingan Outcome Bedah Minimal Invasif dan Bedah Terbuka Dalam Pengelolaan Apendisitis Akut di RSUD Waled Periode 2022- 2024 - Mochamad Raihan Fahrezi; Mohamad Romdhoni; Yukke Nilla Permata (Universitas Malahayati Lampung, 2026)
ABSTRACT Acute appendicitis is one of the most common emergency surgical conditions requiring prompt management. Two primary surgical techniques used are open surgery and minimally invasive surgery. Each method has its own advantages and disadvantages, but local evidence comparing the clinical outcome of both methods remains limited, particularly at RSUD Waled. To compare the outcome of minimally invasive versus open surgery in the management of acute appendicitis at RSUD Waled during the 2022–2024 period, in terms of postoperative wound infection, length of hospital stay, and postoperative pain scale. This was a cross sectional outcome study involving 107 patients with acute appendicitis who underwent surgery at RSUD Waled. Data were obtained from medical records and analyzed using the Chi-Square test to compare outcome between the two surgical techniques. The study showed that patients undergoing minimally invasive surgery had a lower incidence of postoperative wound infection (24%) compared to open surgery (46.3%) (p = 0.047). Shorter hospital stays (4 days) were more common in the minimally invasive group (84%) than in the open surgery group (56.1%) (p = 0.012). Additionally, mild postoperative pain was more frequently experienced by patients who underwent minimally invasive surgery (72%) compared to those who had open surgery (42.7%) (p = 0.010). Minimally invasive surgery provides better clinical outcome compared to open surgery in the management of acute appendicitis at RSUD Waled, particularly in reducing postoperative wound infections, shortening hospital stays, and lowering postoperative pain levels. Keywords: Acute Appendicitis, Open Surgery, Minimally Invasive Surgery. ABSTRAK Mengetahui perbandingan outcome antara bedah minimal invasif dan bedah terbuka dalam pengelolaan apendisitis akut di RSUD Waled periode 2022–2024, ditinjau dari aspek infeksi luka post operasi, durasi rawat inap, dan skala nyeri pascaoperasi. Penelitian ini menggunakan desain cross sectional dengan jumlah sampel sebanyak 107 pasien apendisitis akut yang menjalani operasi di RSUD Waled. Data diperoleh dari rekam medis dan dianalisis menggunakan uji Chi-Square untuk membandingkan outcome antara dua jenis operasi. Hasil penelitian menunjukkan bahwa pasien yang menjalani bedah minimal invasif memiliki angka infeksi luka post operasi lebih rendah (24%) dibandingkan bedah terbuka (46,3%) (p=0,047). Durasi rawat inap 4 hari lebih banyak pada kelompok bedah minimal invasif (84%) dibandingkan bedah terbuka (56,1%) (p=0,012). Selain itu, nyeri ringan lebih sering terjadi pada pasien bedah minimal invasif (72%) dibandingkan dengan pasien bedah terbuka (42,7%) (p=0,010). Bedah minimal invasif memberikan hasil klinis yang lebih baik dibandingkan bedah terbuka dalam pengelolaan apendisitis akut di RSUD Waled, khususnya dalam hal penurunan risiko infeksi luka operasi, pemendekan durasi rawat inap, dan penurunan intensitas nyeri pascaoperasi. Kata Kunci: Apendisitis Akut, Bedah Terbuka, Bedah Minimal Invasif.